2016
DOI: 10.1155/2016/6482050
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrol of Methyl Methacrylate during Photoinduced Nitroxide-Mediated Polymerization in the Presence of Photosensitive Alkoxyamine

Abstract: Photosensitive alkoxyamine 2,2,6,6-tetramethyl-1-(1-phenylethoxy)piperidin-4-yl quinoline-2-carboxylate (PE-TEMPO-Q) was synthesized. Photochemical properties of PE-TEMPO-Q were studied to develop photoinduced nitroxide-mediated polymerization of methyl methacrylate (MMA). Rapid and facile polymerization at ambient temperature with PE-TEMPO-Q as an initiator was confirmed to proceed in a controlled mechanism based on the linear growth in molecular weight combined with relative narrow polydispersity index (1.4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This is not only because of its inability in satisfying the above two criteria but also due to its very small molar absorptivity at the excitation wavelength of 266 nm. On the other hand, the PBN1NAP–NPH molecule not only has a significant absorbance at 266 nm but also belongs to the family of alkoxyamines (molecules of the type – N–O–C−) which are known to possess a very labile O–C bond that easily cleaves, either thermally or photochemically (O–C bond energy ∼20–30 kcal/mol). , In fact, it is because of this property that these molecules are widely used in nitroxide mediated polymerization as initiators. Thus, it could be expected that the PBN1NAP–NPH molecule would undergo a C–O bond cleavage on photoexcitation to form PBN1NAP radical and the NPH radical (Scheme ). Importantly, this photo-cleavage of the diamagnetic PBN1NAP–NPH molecule satisfies both the above crucial conditions: (i) the photocleavage results in the formation of the original PBN1NAP molecule, and (ii) the PBN1NAP molecule would strictly be transient as it would be recaptured by its counter NPH radical.…”
Section: Resultsmentioning
confidence: 99%
“…This is not only because of its inability in satisfying the above two criteria but also due to its very small molar absorptivity at the excitation wavelength of 266 nm. On the other hand, the PBN1NAP–NPH molecule not only has a significant absorbance at 266 nm but also belongs to the family of alkoxyamines (molecules of the type – N–O–C−) which are known to possess a very labile O–C bond that easily cleaves, either thermally or photochemically (O–C bond energy ∼20–30 kcal/mol). , In fact, it is because of this property that these molecules are widely used in nitroxide mediated polymerization as initiators. Thus, it could be expected that the PBN1NAP–NPH molecule would undergo a C–O bond cleavage on photoexcitation to form PBN1NAP radical and the NPH radical (Scheme ). Importantly, this photo-cleavage of the diamagnetic PBN1NAP–NPH molecule satisfies both the above crucial conditions: (i) the photocleavage results in the formation of the original PBN1NAP molecule, and (ii) the PBN1NAP molecule would strictly be transient as it would be recaptured by its counter NPH radical.…”
Section: Resultsmentioning
confidence: 99%
“…The N-alkoxyamine C-O bond is known to be relatively unstable in aerated solutions. [54][55][56][57] The low stability of this bond has previously been exploited in nitroxide-mediated living freeradical polymerization where the nitroxide works as a reversible capping agent. 24 Upon mild heating, homolytic cleavage occurs resulting in the regeneration of the stable radical by which the polymerization continues.…”
Section: Figure 11mentioning
confidence: 99%
“…136 Cui and co-workers, then developed a new UV-sensitive alkoxyamine that facilitated the stereocontrolled NMP of MMA. 137 A light-sensitive alkoxyamine bearing a chromophore was developed in a 2018 study by Guillaneuf and colleagues to control the surface patterning of polymers on silicon wafers. 138 Bonardi et al recently reported the synthesis of various methacrylates using a two component initiating system, where NIR light would be absorbed by a dye that would convert it to heat which would lead to a conventional local thermal polymerization.…”
Section: ■ Photopolymerizationmentioning
confidence: 99%
“…In 2015, Chen and colleagues synthesized a series of photosensitive nitroxides containing different chromophores that were used to photopolymerize MMA with narrow molecular weight distributions . Cui and co-workers, then developed a new UV-sensitive alkoxyamine that facilitated the stereocontrolled NMP of MMA . A light-sensitive alkoxyamine bearing a chromophore was developed in a 2018 study by Guillaneuf and colleagues to control the surface patterning of polymers on silicon wafers .…”
Section: Photopolymerizationmentioning
confidence: 99%